A comparative study of intrathecal morphine and fentanyl as additives to of 0.5% hyperbaric bupivacaine in lower segment caesarean section: A prospective randomized double blind clinical trial - Asif, Mohammad; Waghamore, Neelavati; Hussain, Anwar (Journal of Neonatal Surgery, 2025)
Background And Aims- Addition of small doses of opiods to intrathecal bupivacaine solution improves the quality of sensory blockade and provides better postoperative pain relief. Morphine and fentanyl are the opioids commonly used for this purpose. We aimed to compare analgesic efficacy in terms of post-operative analgesia and adverse effects associated with intrathecal morphine and fentanyl in patients undergoing Lower segment caesarean section. Materials and Methods: - This was Prospective randomized double blind clinical trial, invoving 120 patients undergoing elective lower segment caesarean section under spinal anaesthesia. They were randomly divided into 2 groups, 60 patients in each group, group A received 0.5% hyperbaric bupivacaine 1.8ml with Morphine 100mcg, group B received 0.5% hyperbaric bupivacaine 1.8ml with Fentanyl 25mcg. Primary objective is to measure time taken for request of first rescue analgesic dose secondary objectives is to compare incidence of side effects between both groups. Results: Onset of sensory, onset of motor block was not statistically significant between both groups. Time taken for 2 segment regression of sensory block was significantly higher in morphine group 242.83 ± 28.94 compared to fentanyl group 172.33 ±20.70, p <0.0001,time taken for regression of motor block to bromage 0 was significantly higher in morphine group 216.33 ±117.76 compared to fentanyl group 155.00 ±29.31, p<0.0002. Duration of analgesia that is time for request of first rescue analgesic at VAS score of 4 is significantly higher in morphine group with mean duration of 885.67 ± 216.41 compared to fentanyl group 356.68 ±123.48, incidence of nausea , vomiting , pruritis, shivering did not differ in patients of either group. Conclusion: -We concluded that addition of 100 mcg morphine to intrathecal 0.5% hyperbaric bupivacaine resulted in significantly prolonged duration of postoperative analgesia compared to fentanyl 25mcg without significant side effects.